Universities without Academic Freedom Have No Place in Rankings - Holz, Carsten (International Higher Education, 2021)
Academic freedom plays little or no role in university rankings, yet makes all the difference between a thriving academy and regime-controlled higher education. Adjusting a well-known university ranking to include academic freedom easily shakes out “top” universities under totalitarian regimes. If our values are due more than lip service, then the current system of university rankings is in urgent need of reform.